The relationship between the purposes of the law and legal reasoning - Laluddin, Hayatullah; Mohd. Nor, Amir Husin; Ibrahim, Ibnor Azli; Muhammad Husni, Ahmad; El-Seoudi, Abdel Wadoud Moustafa Moursi; Omar, Anwar Fakhri; Samsudin, Muhammad Adib; Alias, Muhammad Nazir (Medwell Journals, 2012)
It is argued that, since qiyas presents a mechanism for the derivation of rulings from the textual sources of the law, in the light of its purposes, the existence of a relation between qiyas and the purposes of the law can be visualized. For, it is in the light of the consideration of the purposes that the rational of a given text is extended to the cases that do not come under its purview. This article therefore, attempts to highlight and analyze the relation between the purposes of the law and qiyas. It also investigates the literal and technical meanings of qiyas and purposes of the law and evaluates their relation in the light of latter providing justification for the former in respect of extension and restriction of legal rulings. The authors, using descriptive and analytical approach, conclude that the purposes of the law by virtue of their potential role in qiyas (legal reasoning) equip the jurist with the ability and insight in how to apply the rulings strictly and when to mitigate them, a fact underscoring the existence of a strong relation between the two.